Kemampuan Informasi Akuntansi dalam Memprediksi Arus Kas Masa Depan - Lukman, Siti Diva Syarifah (Amsir Accounting & Finance Journal, 2023)
This research is purposed to determine there is a relationship between the information content of accounting which measured by net profit and component of cash flow toward future of cash flow. Data used in this research is secondary data obtained from the database of the Indonesia Stock Exchange (IDX), which can be accessed through the official website www.idx.co.id. Independent variables used net profit before extraordinary items (X1), operating of cash flow (X2), investing of cash flow (X3), financing of cash flow (X4), and future of cash flow (Y) as dependent variable. Based on the result of research was found that (1) net profit before extraordinary items partially have a significant positive influence on the future cash flow, (2) operating of cash flow partially have a significant positive influence on the future of cash flow, (3) investing of cash flow partially do not have a significant positive influence on the future of cash flow, (4) financing of cash flow have a significant positive on the future of cash flow.